Studi Tentang Harga Diri pada Mahasiswa Yang Bekerja Paruh Waktu: (Studi Deskriptif Mahasiswa Program Studi Bimbingan dan Konseling Universitas Sanata Dharma Angkatan 2020-2021 yang Bekerja Paruh Waktu) - Berliani Primasari; Robertus Budi Sarwono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to determine the level of self-esteem in students of the Guidance and Counseling Study Program of Sanata Dharma University Class of 2020-2021 who work part-time, as well as identify items measuring aspects of self-esteem in students of the Guidance and Counseling Study Program of Sanata Dharma University Class of 2020-2021 who work part-time, on the achievement of scores that are identified as poor or less than optimal. This type of research is quantitative descriptive research. The sample of this study was 40 students of the Sanata Dharma University Guidance and Counseling Study Program Class of 2020-2021 who worked part-time. Data collection techniques through surveys with google forms. The number of valid items on the self-esteem scale is 28 items and has a Cronbach Alpha reliability index of 0.961. The results showed that the level of self-esteem in students who work part-time is very high at 55%. The results of this study also show that there are 2 items with moderate score achievements on the self-esteem scale, so there are 2 proposed topics regarding time management and priorities and planning and priorities, which can be used as material for lecturer discussions with students.